bZIPs and WRKYs: two large transcription factor families executing two different functional strategies - Llorca, Carles M.; Potschin, Maren; Zentgraf, Ulrike (Frontiers in Plant Science, 2014)
bZIPs and WRKYs are two important plant transcription factor families regulating diverse developmental and stress-related processes. Since a partial overlap in these biological processes is obvious, it can be speculated that they fulfill non-redundant functions in a complex regulatory network. Here, we focus on the regulatory mechanisms that are so far described for bZIPs and WRKYs. bZIP factors need to heterodimerize for DNA-binding and regulation of transcription, and based on a bioinformatics approach, bZIPs can build up more than the double of protein interactions than WRKYs. In contrast, an enrichment of the WRKY DNA-binding motifs can be found in WRKY promoters, a phenomenon which is not observed for the bZIP family. Thus, the two transcription factor families follow two different functional strategies in which WRKYs regulate each other’s transcription in a transcriptional network whereas bZIP action relies on intensive heterodimerization.